LITERARY DEVICES FOUND IN THE SELECTED POEMS OF GRADE 9 TEXTBOOK - Manatad, Christine Ria Aliphanta; Flores, Yvonne Grace B; Dandasan, Aiana; Catubig, Daisy R; Naparan, Genesis B (Universitas Negeri Yogyakarta, 2025)
The purpose of figurative language is to add creativity and depth to writing. Beauty and artwork make poems more interesting and unique. The study's objectives were to identify the literary devices used in a selected poem from the Grade 9 English Literary Textbook and explain the contextual meaning of each literary device. The researcher categorized the literary devices according to Perrine's model. The findings revealed the identification of ten literary devices. After the analysis, the data showed ten types of literary devices: simile, metaphor, personification, apostrophe, synecdoche, metonymy, symbol, paradox, hyperbole, and irony. The study identified 115 instances of literary devices in the poems, with 5 similes, 28 metaphors, 34 personifications, 2 apostrophes, 4 synecdoches, 3 metonymies, 3 symbols, 6 paradoxes, 13 hyperboles, and 7 ironies. The most prominent literary device was personification, which occurred 34 times. It was also found that the least used literary devices were apostrophes and symbols, each appearing three times. The lesson plan created in this study is based on the Grade 9 textbook and uses the selected poem.